A Novel Lay Health Worker Training to Help Women Engage in Postabortion Contraception and Well-Woman Care. Issue 2 (March 2020) - Chor, Julie; Young, Danielle; Quinn, Michael T.; Gilliam, Melissa
Young women, low-income women, and women of color make up a disproportionate share of abortion patients and experience higher rates of unintended pregnancy, maternal morbidity and mortality, and infant mortality. Furthermore, these individuals are also less likely to have access to preventive gynecologic care. Whereas lay health worker interventions have been developed to help link individuals to care in other fields, the use of such interventions to link individuals to preventive care after abortion is novel. This article describes a training protocol and curriculum that provided nonmedically trained individuals with knowledge, skills, and competency to conduct a behavioral theory–based counseling intervention to help individuals achieve self-identified goals regarding obtaining postabortion reproductive health care and contraception. When piloted with 60 patients presenting for abortion who lacked a regular health care provider and desired to delay pregnancy for at least 6 months, participants found the lay health worker skills and the counseling session highly acceptable. Specifically, participants reported feeling comfortable speaking to lay health workers about contraception and reproductive health care. These findings indicate that lay health worker interventions may present an important opportunity to help individuals address their postabortion preventive and contraceptive health care needs.